Glycol porphyrin derivatives and temoporfin elicit resistance to photodynamic therapy by different mechanisms - Kralova, Jarmila; Kolar, Michal; Kahle, Michal; Truksa, Jaroslav; Lettlova, Sandra; Balusikova, Kamila; Bartunek, Petr (Scientific reports, 2017)
The development of drug resistance is a major problem which often occurs during anticancer chemotherapies. Photodynamic therapy (PDT) has been studied as an alternative treatment modality for drug-resistant tumors, however the question of resistance to PDT and potential cross-resistance with chemotherapy has yet to be fully answered. To investigate the mechanism of resistance to PDT, we developed an in vitro experimental model system in a mouse mammary carcinoma cell line 4T1. We used two ethylene glycol derivatives of tetraphenylporphyrin, and tetraphenylchlorin derivative, temoporfin, as photosensitizers (PS). PDT-resistant clones were obtained by exposure to a set concentration of PS followed by irradiation with increasing light doses. PDT resistance to soluble glycol porphyrins was mediated mainly by increased drug efflux through ABCB1 (P-glycoprotein) as we demonstrated by specific ABCB1 knockdown experiments, which in turn rescued the sensitivity of resistant cells to PDT. In contrast, resistance raised to temoporfin, which is generally more lipophilic than glycol porphyrins, elicited mechanism based on sequestration of the drug to lysosomes. The resistance that is acquired from a particular PS could be overcome by using a different PS, which is not susceptible to the same mechanism(s) of resistance. Elucidation of the underlying mechanisms in various types of resistance might facilitate improvements in PDT treatment design.
Keywords: MCF-7 Cells; ethylenglykoly; paclitaxel; porfyriny; Porphyrins; ATP Binding Cassette Transporter, Subfamily B, Member 1; lidé; Ethylene Glycols; Photosensitizing Agents; fotosenzibilizující látky; fotochemoterapie; Mice; MFC-7 buňky; mesoporfyriny; P-glykoprotein; Gene Knockdown Techniques; Glycols; chemorezistence; ženské pohlaví; zvířata; Humans; Photochemotherapy; nádory mléčné žlázy u zvířat; genový knockdown; myši; glykoly; Paclitaxel; Female; Mammary Neoplasms, Animal; Mesoporphyrins; Drug Resistance, Neoplasm; Animals